Alentejano and Bísaro pigs and their crosses: genotype effect on loin traits - Martins, J.M. (2019)
Alentejano (AL) and Bísaro (BI), the two main Portuguese local pig breeds, cohabited in Ribatejo region for some time, but their crosses disappeared in the 1950’s. Although appreciated, no scientific data is available regarding the Ribatejano (RI) pig (ALxBI or BIxAL) animals or their meat. In order to assess the meat quality of RI pigs, castrated male pigs from AL, BI, ALxBI and BIxAL genotypes were studied within the framework of the TREASURE project. Raised in a traditional free-range system and fed commercial diets ad libitum, ten pigs from each genotype were slaughtered at ~65 (Trial 1) and nine at ~150 kg live weight (LW) (Trial 2). Longissimus lumborum (LL) physical-chemical traits (pHu at 24 h, intramuscular fat (IMF), myoglobin and total collagen) were measured and data statistical analyses were performed by one-way ANOVA. In both trials, BI, ALxBI and BIxAL attained slaughter weight faster, presenting higher ADG than AL pigs, but this difference was only significant (P<0.001) in trial 1 (65 kg). At 65 and 150 kg, % commercial yield was higher (P<0.01 and P<0.05, respectively) in BI than AL pigs, mainly due to heavier loin (P<0.05) and ham (P<0.001) weights in BI pigs. RI crosses presented intermediate values of those presented by the pure genotypes. Conversely, fat cuts (P<0.01) and backfat thickness (P<0.001) were higher in AL than in BI pigs in both slaughter weights, with RI crosses presenting again intermediate values. Physico-chemical data showed that AL pigs presented LL muscle with higher pHu (P<0.01) (trial 1 - 5.57 vs 5.44; trial 2 - 5.72 vs 5.49) and IMF (P<0.05) (trial 1 - 6.7 vs 5.5; trial 2 - 6.9 vs 6.0), higher myoglobin (P<0.05) (trial 1 - 0.76 vs 0.54; trial 2 - 0.86 vs 0.45) and lower total collagen (P<0.05) (trial 1 - 13.9 vs 17.1; trial 2 - 13.1 vs 16.7) content than BI. This last parameter influenced meat tenderness, with lower Warner-Bratzler shear force values in AL than BI pigs (data not shown). As to RI pigs, overall they presented LL with intermediate pHu, slightly lower IMF (more pronounced in trial 1), and identical pigment content and tenderness than the ones of AL pigs. In conclusion, RI pigs presented intermediate traits between the fatter (AL) and the leaner (BI) genotypes. These first results on RI pig’s LL traits, suggest their potential for the production of heavier loins than AL pigs, with identical rich colour and tenderness, and high quality dry-cured products. RI pigs could therefore be an alternative to the use of other breeds on commercial crosses, helping to increase the income of local pig producers, and also maintain or increase the pure breed populations, contributing to animal biodiversity.